Effect of Humidity on Light-Activated NO and NO2 Gas Sensing by Hybrid Materials - Abulkosim Nasriddinov; Marina Rumyantseva; Elizaveta Konstantinova; Artem Marikutsa; Sergey Tokarev; Polina Yaltseva; Olga Fedorova; Alexander Gaskov (Nanomaterials, 2020)
Air humidity is one of the main factors affecting the characteristics of semiconductor gas sensors, especially at low measurement temperatures. In this work we analyzed the influence of relative humidity on sensor properties of the hybrid materials based on the nanocrystalline SnO2 and In2O3 and Ru (II) heterocyclic complex and verified the possibility of using such materials for NO (0.25–4.0 ppm) and NO2 (0.05–1.0 ppm) detection in high humidity conditions (relative humidity (RH) = 20%, 40%, 65%, 90%) at room temperature during periodic blue (λmax = 470 nm) illumination. To reveal the reasons for the different influence of humidity on the sensors’ sensitivity when detecting NO and NO2, electron paramagnetic resonance (EPR) spectroscopy and diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) investigations were undertaken. It was established that the substitution of adsorbed oxygen by water molecules causes the decrease in sensor response to NO in humid air. The influence of humidity on the interaction of sensitive materials with NO2 is determined by the following factors: the increase in charge carrier’s concentration, the decrease in the number of active sites capable of interacting with gases, and possible substitution of chemisorbed oxygen with NO2− groups.